Copine 7 promotes colorectal cancer proliferation through PKM2 interaction and MAPK signaling pathway - Yu, Tianwen; Huang, Changhao; Lai, Chen; He, Qing; Yuan, Weijie; Chen, Zihua (Frontiers in Oncology, 2023)
Colorectal cancer (CRC) is currently the third most common cancer in the world, and its prevalence and mortality rate continue to increase. Based on an analysis of The Cancer Genome Atlas database, we found that Copine 7 (CPNE7) expression varies significantly between colorectal adenocarcinoma tissue and adjacent normal tissue. From the online Tumor Immune Estimation Resource and Gene Expression Profiling Interactive Analysis, we found that CPNE7 is highly expressed in various other tumors as well. Our study explored how CPNE7 promotes CRC cell proliferation and migration in vitro and in vivo. We performed cell proliferation, transwell, wound healing, colony formation, and immunoprecipitation assays, and injected overexpressed and knockdown CPNE7 cells into mouse models. Immunohistochemistry and quantitative polymerase chain reaction analysis showed that high expression of CPNE7 was associated with increased tumor size or extension. Comparing and analyzing transcriptome sequencing between exogenous up-/downregulated CPNE7 CRC cells and the controls, we found that CPNE7 activates a signaling pathway stimulating cancer cell proliferation. Coimmunoprecipitation experiments revealed an interaction between CPNE7 and pyruvate kinase muscle protein (PKM). We also found the activity of mitogen-activated protein kinase (MAPK) signaling is regulated by exogenous CPNE7 expression. These results imply that CPNE7 may promote the progression of CRC by interacting with PKM and initiating the MAPK signaling pathway.